PENINGKATAN DAYA SAING PRODUK LOKAL MELALUI STRATEGI PEMASARAN DAN PENGELOLAAN PELAPORAN KEUANGAN BERBASIS DIGITAL - Silmi, Silmi; Luthan, Elvira; Rahmadoni, Jefril; Oktavia, Fitriyeni; Hidayat, Danny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The purpose of activity is 1). To Organize MBKM. It Meant give the right students to learning outside the campus. So that students can feel the real conditions in the field which is expected to increase student competitiveness 2),Increase IKU UNAND 2. 3). To answer partner problems related to marketing and management aspects in recording financial reports. The training was carried out in the BumNag hall at pakandangan Emas Pariaman. The training event was attended by employees from Bumnag Padangangan as well as regional officials. Training on implementation methods with a material presentation system followed by questions and answers and bringing in products needed by Bumnag Pakandangan, including galo-galo colonies. As a result of this training, BUMNAG employees learned about the importance of marketing strategies and the existence of applications that can be used easily and safely. The hope is that Bumnag Pakandangan can manage its business lines better and more standardized.Keywords: Marketing Strategy, Local Products, Competitiveness, Digital-Based Financial Reporting